Quantitative study of the indian ethnobotanical medicinal plant resources in the remote Zanskar Valley of Ladakh - Jishtu, Vaneet; Moran, Ankush; Ibrahim, Mohammad; Ahmad, Zabir (Ethnobotany Research and Applications, 2025)
Background: The urgent need for ethnobotanical studies arises from the critical role they play in preserving indigenous knowledge and native biodiversity, which are crucial for sustainable development and the conservation of medicinal plants in a rapidly changing environment. This study explores the ethnomedicinal knowledge of indigenous communities in the remote Zanskar Valley of Ladakh (India), specifically examining the medicinal plant species used in their traditional healing practices. Methods: Semi-structured interviews, informal discussions and snowball sampling were performed to identify individuals with notably greater expertise regarding the uses of resources. The significance level among different parameters was obtained by performing two-tailed independent sample t-test. The ethnobotany R package, used within the R programme, was applied for creating the chord diagrams. Results: In total, 203 informants took part in the study representing a range of age groups and different educational background. The research identifies 55 medicinal plant species, belonging to 50 genera and 28 families, with herbs (78.18%) being the most common growth form. Leaves (43.64%) formed the most commonly utilized plant part, followed by entire plants (36.36%) and roots (18.18%). The use value (UV), relative frequency citation (RFC), and relative importance index (RI) reveals that Corydalis govaniana and Carum carvi are the most valued species. Informant consensus factor (ICF) and fidelity level (FL) indices highlighted the popularity of Podophyllum hexandrum for menstrual irregularity and Cicer microphyllum for skin disorders. Conclusions: The present study conducted in Zanskar valley shows that, regardless of education levels, both young and old generations possess a strong knowledge of medicinal plants, with a clear preference for traditional healing practices over modern medicine. Keywords: Biodiversity, Ethnomedicinal knowledge, Key informants, Medicinal plants, Traditional healing, Zanskar, Ladakh